The patterns of liquid-phase hydrogen peroxide decomposition over transition metal oxides anchored on mesoporous carbon surface - A. A. Gordienko; A. A. Sokolova; V. R. Flid (Тонкие химические технологии, 2014)
The article is devoted to peculiarities of liquid phase hydrogen peroxide decomposition over transition metal (Ag, Cu, Rh, Pd, N or Co) oxides anchored on mesoporous carbon support. The values of activation energy (Ea) and frequency factor (k0) of the catalytic reaction have been determined with kinetic data at 25–70°C. The reaction rate has been established to depend on the strength of the bond between the transition metal anchored and reactive oxygen species adsorbed. The contribution of free radical mechanism has been estimated with inhibitors of free hydroxy (HO∙) and super-oxide (O2 - ) radicals, e.g., dimethylsulfoxide and potassium chloride, respectively. The mechanism of the liquid phase hydrogen peroxide decomposition over the anchored transition metal oxides has been suggested to involve the formation of surface oxygen-containing transition metal complexes, their decomposition being the limiting step of the reaction.